Edukasi Pendidikan Kesehatan Pada Pasangan Usia Subur Dalam Pemilihan Kontrasepsi: Health Education Education for Couples of Childbearing Age in Choosing Contraception - Samsi, Samsi Narti; Rufaridah, Anne; Marlia, Sri; Dahlan, Asmita; Komalasari, Wuri; Husni, Lailatul (Chakra Brahmanda Lentera Institute, 2023)
Family planning is a government program designed to balance needs and population to control the rate of population growth. In the selection of contraceptives that are influenced by age, occupation, education, knowledge and attitudes, availability of health services, and family support. The factors mentioned above are important things to know because they can influence a person's decision making in using contraceptives. The method of this activity is to provide education through health counseling which is held twice in 2 weeks. Counseling was given regarding health education education to couples of childbearing age in choosing contraception . There were 32 couples of childbearing age who took part in educational activities. The media used are leaflets, infocus and laptops. The choice of the type of contraception using the injection method increased by 71.87% to 78.12% with 23 to 25 couples of childbearing age who chose the injection contraceptive method. After education, the dominant couples of childbearing age used contraception, namely 78.12%, planned to continue using this type of contraception through injection, but there was an increase in planning to participate in norplant contraception participants, namely 6.12% and KB tubebectomy/vasectomy 3.12%. This is possible after getting an explanation and understanding and the desire to be able to provide a brighter future for the family by choosing a solid contraception with sufficient number of children they already have. In order to support services and increase public understanding of reproductive health, community service activities are held in the form of Reproductive Health Education and Reproductive Rights for Couples of Reproductive Age in Family Planning services, Kubu Dalam Parak Parakah Village.